Government, politics, and law. Research careers for American Indian/Alaska Native nurses: pathway to elimination of health disparities. - Henly SJ; Struthers R; Dahlen BK; Ide B; Patchell B; Holtzclaw BJ (American Journal of Public Health, 2006)
The health status of American Indians/Alaska Natives lags behind that of the US population. American Indian/Alaska Native (AIAN) nurses are on the front lines of health services for AIAN people. They have the potential to make scientific contributions as well, but are under-represented among researchers working to understand health disparities.The AIAN MS-to-PhD Nursing Science Bridge, at the University of Minnesota, in partnership with the Universities of North Dakota and Oklahoma, provides support for AIAN nurses during the critical training transition from masters of science to doctoral programs. Partner schools collaborate with AIAN elders, medicine people/spiritual leaders, and academic consultants to (1) foster academic success and strengthen the AIAN identity of students during their research training and (2) bring about institutional change to optimize student experiences. Future research programs developed by this cadre of AIAN nurse scientists will contribute scientifically sound, culturally acceptable knowledge to effectively improve the health of AIAN people.